Viral Live‐Attenuated Vaccines (LAVs): Past and Future Directions - Yan‐Dong Tang; Yuming Li; Xue‐Hui Cai; Xin Yin (Advanced Science)
Abstract Viral infections continue to pose a significant threat to the health of both humans and animals. Currently, live attenuated vaccines (LAVs) remain the most efficacious and widely utilized tool for combating viral infections. Conventional LAVs involve the adaptation of virulent viruses to novel hosts, cell cultures, or suboptimal environments, resulting in a reduction in pathogenicity while retaining immunogenicity. This process entails directed evolution of the virus to enhance its replication efficiency under these modified conditions. In this review, the development of traditional animal‐adapted and cold‐adapted LAVs is specially discussed. Additionally, the factors that contribute to virus attenuation from a viral lifecycle perspective are summarized. Finally, we propose future directions for next‐generation LAVs.